A multi‐proxy based high‐resolution stratigraphical analysis of the possible Palaeocene–Eocene boundary interval, Salt Range, Pakistan. (25th August 2020) - Hanif, Muhammad; Sabba, Mahnoor; Ali, Nowrad; Rahman, Maqsood Ur; Ali, Fahad; Swati, Muhammad Azhar Farooq
Abstract : The Palaeocene–Eocene boundary (PEB) interval has been recognized in the Patala Formation, Nammal Gorge Section, Pakistan using lithostratigraphy, stable carbon isotope stratigraphy and integrated biostratigraphy. Four distinct lithological units are identified in the Patala Formation in stratigraphic order from bottom to top; unit‐1 to unit‐4. The top of unit‐3 hosts three closely spaced unconformities demarcated as U1, U2, and U3. The PEB interval is represented by a negative shift of 1.61‰ in δ 13 CV‐PDB representing the carbon isotopic excursion (CIE) in unit‐2. Based on the encountered foraminifera, dinocysts, and calcareous nannoplanktons, the following biozones are identified across the PEB; two larger benthonic foraminiferal (LBF) zones (SBZ4 and SBZ5), the zonal boundary slightly postdating the CIE, two smaller benthonic foraminiferal zones (BB1 and BB2), three planktonic foraminiferal zones (P4/P5 + E1), four dinocysts zones (Pak‐DV, Pak‐DVI, Pak‐DVII, Pak‐DVIII), and two calcareous nannoplankton subzones (NP9a and NP9b). The following protist, dinocyst and calcareous nannoplanktons encountered in the studied interval advocates for the placement of the possible PEB at the level between samples NAM‐SH‐07 and 08; 1—presence of the smaller benthonic foraminifera Angulogavelinella avnimelechi diagnostic of the base of the CIE and the benthonic extinction event (BEE) Tethys wide, 2—presence of the cosmopolitan and the PEB diagnostic dinocyst species ' Axiodinium augustum ', 3—presence of the PEB diagnostic Rhomboaster‐Discoaster calcareous nannoplankton assemblage. The LBF species Alveolina vredenburgi [a marker species of the Larger Foraminiferal Turnover (LFT) associated with the Palaeocene Eocene Thermal Maximum (PETM) and PEB in western Tethys] occurs slightly above the onset of the CIE. Previously reported compositional change in the LBF assemblage from the Salt Range [i.e. the replacement of the Palaeocene orbitoidiform LBF ( Setia and Orbitosiphon ) by the Eocene LBF (Orthophragminids, Alveolina, Nummulites and Assilina )] also postdates the PEB interval here. The late appearance of Alveolina vredenburgi and the compositional change in the LBF after the onset of the CIE are attributed to the facies variation across the PEB reflecting fluctuating depositional environment due to the active tectonic across this interval. This fluctuation is evident from the smaller benthonic and planktonic foraminiferal dominating assemblages in unit‐2 representing bathyal settings followed by LBF dominating unit‐3 representing shallow carbonate platform settings. The change in LBF assemblage closely resembles the well‐known LFT associated with the PETM as well as the carbonate platform stage III and the PEB reported from other Tethyan sections.